Aspectos epidemiológicos e clínicos de pacientes com acidente vascular cerebral isquêmico submetidos ao tratamento endovenoso com ativador tecidual de plasminogênio humano recombinante - rtPA - NASCIMENTO, Kleiton Gonçalves do (2015)
Stroke is considered as the most responsible for the loss of motor function and cognitive in adults. Currently, the only medical treatment for stroke is intravenous thrombolysis with tissue plasminogen activator recombinant human - rtPA. This treatment is not without complications and strict adherence to protocols for all health care professionals is required. In Brazil, there are few data on the implementation of this treatment in the country. This is a retrospective cohort study based on chart review of patients with ischemic stroke treated with intravenous thrombolysis in a public and teaching hospital. Demographic characteristics, comorbidities, clinical stroke severity and response times have been described. Association tests were performed between comorbidities and times of the stages of care with the occurrence of transformation symptomatic hemorrhage. The sample consisted of 64 charts of patients with ischemic stroke undergoing specific treatment. There was a high frequency of comorbidity, more severe neurological deficits in stroke scored the NIHSS scale. The median score on the scale National Institutes of Health Stroke Scale was 15 (SD: 5.3), and the mean time between onset of symptoms and arrival at the hospital was 98 minutes (SD: 61.2). The average time between onset of symptoms and treatment with thrombolytic was 191, 4 minutes (SD: 53) and the average time between the arrival at the hospital and the administration of thrombolytic agent was 89.8 minutes (SD: 39.8). It was observed 20 patients with symptomatic hemorrhagic transformation. In the bivariate analysis, the occurrence of symptomatic hemorrhagic transformation was associated with greater clinical severity of stroke with NIHSS score of> 15 points and presence of comorbidities atrial fibrillation and heart disease. There was significant improvement in neurological deficits assessed by the stroke scale NIHSS between admission and discharge with reduction of the scores (51% to 12.5% among critically ill patients). Intravenous therapy with recombinant human tissue type plasminogen activator - rtPA proved to be effective in improving neurological severity level of patients with ischemic stroke. Improvements are needed from both the forward flow of patients with acute stroke as the clinical protocol in the hospital study. The clinical severity of the stroke and the the presence of comorbidities such as atrial fibrillation seem to be associated with a higher chance of symptomatic hemorrhagic transformation related to treatment with tissue plasminogen activator recombinant human – rtPA.